Estimating the production of withaferin A and withanolide A in Withania somnifera (L.) dunal using aquaponics for sustainable development in hill agriculture - Singh, Manali; Bhutani, Shivani; Dinkar, Nisha; Mishra, Anita; Perveen, Kahkashan; Alfagham, Alanoud T.; Khanam, Mehrun Nisha; Bhatt, Santosh Chandra; Suyal, Deep Chandra (Frontiers in Plant Science, 2023)
Humanity is suffering from huge and severe difficulties, including changes in climate, soil degradation, scarcity of water, and the security of food and medicines, among others. The aquaponics system acts as a closed loop consisting of aquaculture elements and hydroponics, which may contribute to addressing these problems. The aquaponics method is quickly expanding as the requirement to increase the production of sustainable herbal products, including medicinal compounds and foods, in freshwater systems and replenish phosphorous reserves shrinks. The current work is designed to increase the production of the antioxidants withaferin A and withanolide A in two varieties (Jawahar-20 and Poshita) of W. somnifera using the aquaponics technique. Total 100 seedlings (one month old) grown in soil initially were taken to be grown in aquaponics for a time period of 6 months .And 100 seedlings were placed in pots containing soil as control for study after six months. It was observed that the higher content of withaferin A was analyzed in the root and stem samples of Jawahar-20 and Poshita from the sixmonth-old plant of W. somnifera. The maximum content of withanolide A was examined in the root samples of the six-month-old plants of Poshita (1.879 mg/g) and Jawahar-20 (1.221 mg/g).While the 6 month old Poshita seedling grown in soil recorded less withaferin A (0.115±0.009 b ) and withanolide A (0.138±0.008 d ). It is concluded that Poshita was found to be more promising for the enhanced production of withaferin A and withanolide A in the aquaponics system. Moreover, the root was observed as the best source for the production of withaferin A and withanolide A and the best age of the plant is 2 years for the production of bioactive compounds.Thus aquaponics can be an effective approach with enhanced yield of bioactive compounds in medicinal plants with futuristic perspective to hill agriculture and integrated farming.